Destigmatization Strategies of Serbian Londoners on Social Media. (January 2022) - Vico, Sanja
This article looks at banal expressions of nationalism and cosmopolitanism among Serbian Londoners on social media. The findings of this ethnographic research and in-depth interviews show that most participants perceive Serbian national identity as stigmatized due to the legacy of the civil war in the 1990s. Most participants hence employ different strategies in coping with the perceived stigma and redefining what it means to be Serbian. These strategies depend on the period of migration, the affordances of social media, and intended publics. Banal nationalism and banal cosmopolitanism are often manifestations of these strategies on platforms such as Facebook, Instagram, and Twitter with an aim to correct national identity, by presenting it either as superior or as cosmopolitan and exotic difference.